Hypertensive Disorders in Pregnancy and Gestational Diabetes: Does Weight Gained in Pregnancy Matter? [29I]. (May 2018) - Reed, Christina C.; Longo, Monica; Chiossi, Giuseppe; Landgren, Rachel; Chauhan, Suneet; Huff, Cristina Wallace
Abstract : INTRODUCTION: The Institute of Medicine (IOM) released guidelines to optimize weight gain in pregnancy and prevent adverse outcomes. Our aim was to assess the role of pre-pregnancy BMI and maternal weight gain (MWG) as risk factors for hypertensive disorders (gestational hypertension or preeclampsia) and gestational diabetes (GDM). METHODS: A retrospective study reviewed weight gain during pregnancy including: women ages 18-45, singleton, prenatal care <20 weeks, no fetal anomalies, BMI ≥18.5, pre-pregnancy BMI and maternal weight at delivery. A multivariate logistic regression was used to determine the odds ratio (OR) of a composite maternal outcome (CMO) of hypertensive disorders and GDM, according to patient's pre-pregnancy BMI (≥30 vs <30) and MWG (≥ vs < IOM recommendations per BMI category/trimester). RESULTS: Of the 494 women that met the inclusion criteria, 36% were obese and more than 50% had excessive weight gain in the 2nd and 3rd trimester. CMO was present in 22% of the study population. Obese women were more likely to develop the adverse CMO compared to normal/overweight women (p<0.01), and to deliver earlier (37.8±3 vs 38.3±2 weeks, p<0.02). Obese patients followed the IOM recommendations for MWG in the third trimester (100/176 vs 158/318, p=0.047). Multivariate logistic regression showed that obesity at entry to care, not trimester specific MWG, is associated with the composite outcome (aOR 2.0 with 95% CI 1.2-3.5; p<0.01). CONCLUSION: Pre-pregnancy BMI, more than MWG per trimester, significantly contributes to the onset of hypertensive disorders and GDM in pregnancy. Preconception counseling should focus on weight optimization before conception to improve maternal outcome.